Development of Karonda Juice Supplemented Whey Beverage with Enhanced Antioxidant Activity - , Navdeep JP, Ramesh V, Ashish Dixit, Manju G, Manoj Kumar Jaipal, Amit Kumar (Archives of Current Research International, 2025)
This study assessed the antioxidant activity, sensory characteristics, and storage stability of whey-based beverages supplemented with karonda juice. Beverages prepared with varying concentrations of Karonda juice (6, 8, 10, 12, 14%) showed a significant increase in antioxidant activity with increasing juice concentration, while variations in sugar content showed no significant effect. The beverage prepared using 10% sugar supplemented with 14% karonda juice showed highest acceptability by sensory evaluation. The antioxidant capacity of the supplemented beverages was significantly higher than that of paneer whey, with ABTS and DPPH assay values increasing to 5.65±0.03 and 3.99±0.04, respectively. The product ​​remained acceptable for up to three weeks based on seonsory assessment. These findings suggest that karonda juice has the potential to enhance both the antioxidant capacity and sensory appeal of whey-based beverages, while maintaining an acceptable shelf life of three weeks under refrigerated conditions.